THE SHIFT OF THE “TANDAK KISSING” RITUAL CEREMONY IN MADURA ETHNICS MENGANTI GRESIK: ETHNOLINGUISTICS STUDY - Dewanto (Indonesian language and literature education program Majapahit Islamic University, 2025)
The ceremony is a tradition of the community historically has a meaning to give thanks to God and the ancestors of the local community. In accordance with the development of modern society, a culture and tradition begin to slowly shift. This confusion can be seen in the ritual ceremony of tandak kissing (Java language: traditional singer). The tandak kissing ceremony is a traditional ceremony carried out by the ethnic Madurese people who have lived in Menganti Gresik for a long time ago. The ritual ceremony has undergone a shift, because it can be known by the loss or decrease of the community to carry out and keep the ceremony well as a result of social changes. This research method used a qualitative descriptive approach to find out how far the shift occurred and what caused the ceremony to become extinct. This theory used ethnolinguistic studies, which combine linguistic and anthropological aspects to understand the relationship between language and culture. Based on the results of the study, it can be seen that the shift of ritual ceremonies is an effort to find out the extent to which the loss of culture and tradition can occur so that the younger generation can maintain and preserve as a legacy of local wisdom from their ancestors. Keywords: tradition, ceremonies, and rituals